Prospective Clinical Outcomes Following Microfracture Surgery For Isolated and Multi-Site Defects: Mid-Term Follow-Up. Issue 7 (21st July 2017) - Erickson, Brandon J.; Locker, Philip H.; Cvetanovich, Gregory L.; Tilton, Annemarie K.; Gitelis, Matthew E.; Weber, Alexander E.; Yanke, Adam Blair; Cole, Brian J.
Objectives: The purpose of the current study was: 1) to evaluate the outcomes of patients who underwent microfracture and 2) to determine the patient-related and defect-related factors associated with outcomes including factors predicting additional surgery. Methods: Patients who underwent microfracture for focal chondral defect(s) of the knee were eligible. Patients were excluded if concomitant procedures violated the subchondral bone. Outcomes were determined using preoperative and final follow-up patient reported outcomes (PROs) including; IKDC, KOOS, WOMAC, SF-12 and Overall Satisfaction. Patient-related factors and defect-related factors were analyzed for correlations with outcome. All patient-related and defect-related factors were also analyzed as predictors for subsequent surgery. Results: Overall 101 patients (55M/46F) mean age: 35.9±12.5 years, BMI 26.3±5.5 kg/m2, mean defect size: 2.64±1.81 cm2 underwent microfracture and met enrollment criteria. Lesion location included: 44.90% medial femoral condyle, 21.43% trochlea, 11.22% lateral femoral condyle, 10.20% multiple site, 8.16% patella, and 4.08% tibial plateau. In 72 of 101 (71%) knees, microfracture was performed in insolation. At mean follow-up of 5.7±2.5 years, statistically significant and clinically meaningful improvements (MCID and MCD) were seen in all PROs (p<0.05), aside from SF-12 mental scores which improved although not significantly (p=0.07) (Figure 1). Increased age, higher BMI, isolated tibial microfracture, multi-site microfracture and increased defect size all correlated with lower final follow-up PROs (p<0.05). Males demonstrated greater magnitude of improvement in KOOS symptoms and sports subscales (p=0.006 and p=0.037). In the multivariate analysis, larger defect size (>3.6 cm2) and prior knee surgery were independent risk factors for additional knee surgery. Conclusion: Following microfracture all patients demonstrated significant and clinically meaningful improvements in outcomes at a mean of 5.7 years. Increasing age and BMI are the patient-related factors that may predict a poor outcome. Defect-related predictors of poor outcome include microfracture of tibial lesions and multi-site microfracture as compared to isolated femoral defect microfracture. Larger lesion size (>3.6 cm 2 ) and a history of prior knee surgery may predict the need for additional knee surgery following microfracture.